Molecular Evolution of Phototransduction Pathway Genes in Nocturnal and Diurnal Fireflies (Coleoptera: Lampyridae) - Martin, Gavin J. (Insects, 2021)
SIMPLE SUMMARY: Animal groups differ in the primary sense (touch, taste, smell, vision, hearing) that they use to perceive the world around them. Discovering how evolution has shaped animal senses is essential to understanding how animals interact with their environments. Fireflies are a wonderful creature to study since they use bioluminescence to find mates at night, but there are some firefly species that use other means (e.g., pheromones) to find mates and fly during the day. We examined the genes that are expressed in the eye that support sight to see if there were patterns of evolution on specific genes and different patterns of selection between day-flying non-bioluminescent and nocturnal bioluminescent fireflies. Our research is unique among beetles and is complementary to work done in flies, butterflies, and moths and allows us to better understand the boundaries of evolution on the animal visual system. ABSTRACT: Most organisms are dependent on sensory cues from their environment for survival and reproduction. Fireflies (Coleoptera: Lampyridae) represent an ideal system for studying sensory niche adaptation due to many species relying on bioluminescent communication; as well as a diversity of ecologies. Here; using transcriptomics; we examine the phototransduction pathway in this non-model organism; and provide some of the first evidence for positive selection in the phototransduction pathway beyond opsins in beetles. Evidence for gene duplications within Lampyridae are found in inactivation no afterpotential C and inactivation no afterpotential D. We also find strong support for positive selection in arrestin-2; inactivation no afterpotential D; and transient receptor potential-like; with weak support for positive selection in guanine nucleotide-binding protein G(q) subunit alpha and neither inactivation nor afterpotential C. Taken with other recent work in flies; butterflies; and moths; this represents an exciting new avenue of study as we seek to further understand diversification and constraint on the phototransduction pathway in light of organism ecology.